2016
DOI: 10.1186/s12872-016-0379-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and coronary heart disease mortality: a meta-analysis of prospective cohort studies

Abstract: BackgroundHyperuricemia may be associated with an increased risk of coronary heart disease (CHD) mortality; however, the results from prospective studies are conflicting. The objective of this study was to assess the association between hyperuricemia and risk of CHD mortality by performing a meta-analysis.MethodsPubmed and Embase were searched for relevant prospective cohort studies published until July 2015. Studies were included only if they reported data on CHD mortality related to hyperuricemia in a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
82
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 59 publications
6
82
1
7
Order By: Relevance
“…Previous studies have also reported a relationship between HUA and CAD [4, 1012]. Some of the results confirmed a strong association between HUA and CAD; however, most of the results focused on the relationship between HUA and the risk of CAD in a middle-aged and elderly population [11, 13].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have also reported a relationship between HUA and CAD [4, 1012]. Some of the results confirmed a strong association between HUA and CAD; however, most of the results focused on the relationship between HUA and the risk of CAD in a middle-aged and elderly population [11, 13].…”
Section: Discussionmentioning
confidence: 85%
“…For instance, higher SUA levels appear to be protective against progression of Parkinson’s disease in men, but not women [21]. Other lines of research show that the association between SUA and cardiovascular disease is stronger in women compared to men [2225]. For instance, a recent meta-analysis found that hyperuricemia had a stronger association with coronary heart disease mortality in women compared to men [25].…”
Section: Introductionmentioning
confidence: 99%
“…High SUA levels are a strong and independent marker of impaired prognosis in patients with moderate-to-severe chronic heart failure 11 . In addition, a recent meta-analysis found that hyperuricemia might increase the risk of coronary heart disease and all-cause mortality 12 .…”
Section: Introductionmentioning
confidence: 99%